The effect of price, promotion, and product quality on the purchase decision of Rinso detergent in Surabaya - Yandri Samuel Augusteyn; Sardina Sobeukum (Jurnal Bisnis Mahasiswa, 2026)
Purpose – This study aims to analyze the influence of Price, Promotion, and Product Quality on Purchase Decision for Rinso detergent in Surabaya. Design/methodology/approach – The research employs a quantitative, explanatory research design. A total of 330 respondents, active consumers of Rinso detergent, were selected through purposive sampling based on criteria such as regular purchase behavior and experience with the variables studied. Data were collected using a structured questionnaire and analyzed using multiple linear regression to evaluate both simultaneous and partial effects of Price, Promotion, and Product Quality on Purchase Decision. Findings – The results indicate that Price, Promotion, and Product Quality all have a significant effect on Purchase Decision. Price is the most dominant factor, followed by Promotion and product quality. Research limitations – This study is limited to consumers in Surabaya and focuses only on three elements of the marketing mix. Future research could expand the geographic scope, include additional marketing variables such as distribution or brand image, and adopt longitudinal designs to capture changes in consumer behavior over time. Implications – The findings suggest that companies should develop integrated marketing strategies that consider Price, Promotion, and Product Quality simultaneously to enhance consumer value, loyalty, and brand competitiveness. These insights are particularly useful for detergent manufacturers targeting urban markets like Surabaya. Originality – This study combines Marketing Mix theory and Consumer Behavior theory to examine Purchase Decision from both consumer and business perspectives, offering a dual-perspective approach to understanding and applying marketing strategies.